The Kingdom of Saudi Arabia: More on Determining the Model of Arab Nationhood - V. V. Naumkin; V. A. Kuznetsov (Сравнительная политика, 2024)
The article is consecrated to exploring the genesis and specific features of the Saudi political system, viewed as a variant of nationhood model, that was shaped in the 20th century in the Arab world and appeared to be in the grip of crisis over the second and third decades of the 21st century. The research is based on a hybrid historic-politological methodology that permits to trace the genesis and evolution of the political system throughout a protracted period in retrospect. The source base of a historic research section is made up of documents compiled by Soviet diplomats as well as diplomatic records of the Kingdom of Saudi Arabia, which detail the steps undertaken by Ibn Saud with the aim of setting up the institutes of political power in the Kingdom and defining its administrative and territorial structure. Drawing on these documents, the politological section of this article identifies three clusters of elements pertinent to the Saudi political model: a universal cluster, whose analogues can be found in the history of diverse state formations, an Arab-Muslim cluster, which is in correlation with the appropriate political culture, and an Arabian one. Other examples are revealed, where the above elements of nationhood have played a crucial role. The Saudi specificity, as shown herein, embraces both traditional and contemporary elements of statehood. A thesis is advanced by the authors regarding the existence of a specifically Arabian model underlying the genesis of a multicomponent state, also the ramifications of such genesis for the development of political system are laid out.